Using 2-D electrical resistivity imaging for joint geophysical and geotechnical characterization of shallow landslides - Crawford, Matthew M.; Bryson, L. Sebastian; Woolery, Edward W.; Wang, Zhenming (Journal of applied geophysics, 2018)
Electrical resistivity has become an increasingly popular technique for landslide investigations, providing insight into landslide type, location of the failure zone, differentiating soil and bedrock interfaces, and identifying areas of excess moisture. Using electrical resistivity as a tool to assess geotechnical properties of the landslide mass is often underutilized, however. Geophysical and geotechnical data sets for landslide investigations are commonly acquired independently in order to answer different questions. The non-unique solutions to electrical resistivity measurements are rarely correlated with geotechnical properties, such as water potential and shear strength. This study presents electrical resistivity data collected at two shallow colluvial landslides in Kentucky. A field-based framework was developed using modified soil-water characteristic curves and in-situ electrical conductivity measurements that allows 2-D electrical resistivity measurements to be a predictor of shear strength. The methodology incorporates in-situ field measurements of volumetric water content, water potential, and electrical conductivity within a framework to demonstrate that surface electrical resistivity can be used to highlight strength throughout the slope. •Electrical resistivity used to interpret landslide type, failure zones, lithology, and changes in moisture conditions.•The time-lapse difference inversions reflect changes in moisture conditions and porosity during slope movement.•A field-based framework that allows 2-D electrical resistivity measurements to be a predictor of shear strength.